Additive anti-inflammatory effects of corticosteroids and phosphodiesterase-4 inhibitors in COPD CD8 cells. Issue 1 (December 2016) - Grundy, Seamus; Plumb, Jonathan; Kaur, Manminder; Ray, David; Singh, Dave
Abstract Background CD8 lymphocytes play an important role in the pathogenesis of COPD. Corticosteroids and phosphodiesterase 4 (PDE4) inhibitors are anti-inflammatory drugs used for COPD treatment. Little is known of the combined effect of these drugs on COPD CD8 cells. We studied the effect of corticosteroid combined with PDE4 inhibitors on cytokine release form circulating and pulmonary CD8 cells, and on glucocorticoid (GR) nuclear translocation. Methods The effect of dexamethasone alone and in combination with the PDE4 inhibitors roflumilast and GSK256066 on cytokine release from circulating and pulmonary CD8 cells was measured. The effect of the compounds on nuclear translocation of GR and cyclic AMP-responsive element-binding protein (CREB) was studied using immunofluorescence. Results Dexamethasone inhibited cytokine release from COPD CD8 cells in a concentration dependent manner. PDE4 inhibitors enhanced this anti-inflammatory effect in an additive manner. PDE4 inhibitors did not increase corticosteroid induced GR nuclear translocation. PDE4 inhibitors, but not corticosteroid, increased phospho-CREB nuclear translocation. Conclusion The combination of corticosteroids and PDE4 inhibitors results in an additive anti-inflammatory effect in COPD CD8 cells. This enhanced anti-inflammatory effect could translate to important clinical benefits for patients with COPD.